Catheter‐related right atrial thrombus in sickle cell disease. Issue 11 (20th September 2017) - Zhao, Chen; Sathya, Bharath; Nadal Rios, Rosa; Arai, Andrew E.; Brofferio, Alessandra; Thein, Swee Lay; Ruhl, A. Parker
Key Clinical Message: Catheter‐related right atrial thrombus (CRAT) can occur in patients with sickle cell disease, particularly if additional risk factors for thrombosis are present. Cardiac MRI may differentiate thrombi from other types of atrial masses. Treatment should include anticoagulation and the timing of catheter removal should balance the potential risk of embolization. Abstract : Catheter‐related right atrial thrombosis (CRAT) can occur in patients with sickle cell disease, particularly if additional risk factors for thrombosis are present. Cardiac MRI may differentiate thrombi from other types of atrial masses. Treatment should include anticoagulation and the timing of catheter removal should balance the potential risk of embolization.